The 28-spotted potato ladybird beetle Henosepilachna vigintioctomaculata (Motsch.) in Primorsky kray: the history of the pest (review) - M. V. Ermak; N. V. Matsishina; P. V. Fisenko (Овощи России, 2022)
The 28-spotted potato ladybird beetle is an endemicspecies of the Russian Far East. Nowadays the potato ladybird beetle is widespread across Primorsky and Khabarovsky kray, south Sakhalin, Kunashir Island, and in China, Japan, and India. This paper presents historical data on the dispersal of the potato ladybird beetle in Russia. The first records of the pest presence in the coastal area of Primorsky kray were made in 1929. In the 1950s and 1960s, the pest was observed to inhabit not only the forest steppe zone and the districts adjacent to the taiga in Primorsky kray, but also Khabarovsky kray, Amur oblast and Jewish autonomous oblast. The process of dispersal of the potato ladybird beetle can be divided in several stages: the formation of a new breeding ground, an increase in the size of the pest population, the dispersal of the pest. The range expansion of the potato ladybird beetle can be linked to two facts. First, the land area under potato cultivation increased and neared the breeding grounds of the pest. Secondly, thedietary preference of the phytophagous insect shifted to the new fodder plant. In addition, the development of transportation routes played an important role in the dispersal of the pest. Therefore, anthropogenic factors significantly affected the distribution of the potato ladybird beetle. These factors in combination with a high ecological plasticity of the pest allowed the phytophagous insect to spread across the whole area under potato cultivation in the south of the Russian Far East.